The impact of the perceived leader’s empathy, group commitment, and individualism/collectivism on cooperation : an experimental study - Martins, Catarina Geraldes Freire (2021)
Humans have been cooperating for hundreds of years, even though, on some occasions and especially in highly competitive environments, there are no logical reasons for them to do so. Why? What leads people to cooperate? The present research aims to answer this question by identifying three main dimensions that can impact cooperation: the individual’s tendencies for individualistic or collectivistic attitudes, the level of commitment towards the group, and the perceived leader’s empathy. In order to study these topics, a “Public Goods Game”, with monetary contingencies, was organized involving the participation of 256 subjects. The empathy displayed by the leader was manipulated (empathic, neutral, and non-empathic leader), whilst collecting data regarding the participant’s levels of group commitment and individualism/collectivism. Participants were also divided between participating and non-participating leader groups depending on the presence of the leader within the group. Results showed that there was no significant difference between the conditions with distinct empathy and cooperation. Moreover, group commitment was found to be positively related to cooperation and individualism negatively related to cooperation. Some measurements of group commitment and individualism/collectivism were found as significant predictors of cooperation. This was the case for normative group commitment (positive predictor), competitiveness and supremacy of individual interests (negative predictors). The participation of the leader within the group and the interaction between participation and empathy of the leader did not create an impact on cooperation.